Medication beliefs and adherence during and after pregnancy among women at risk for gestational hypertensive disorders - Dreesen, Pauline; Lanssens, Dorien; Nouwen, Sandy; Volders, Pauline; Janssen, Febe; Soubry, Adelheid; Gyselaers, Wilfried; Ceulemans, Michael (Frontiers in Drug Safety and Regulation, 2025)
IntroductionLow-dose aspirin initiated ≤16 weeks of gestation reduces the risk of developing early-onset preeclampsia. However, no recent data are available on women’s beliefs about medication and adherence in pregnant women at risk for gestational hypertensive disorders (GHD). This study aimed to evaluate medication beliefs and adherence in this high-risk population, and to explore the relationship between adherence, self-reported aspirin intake, and pregnancy and neonatal outcomes.MethodsPregnant women at risk for GHD followed up via remote blood pressure monitoring and who were prescribed aspirin 160 mg/day were included (ClinicalTrials.gov ID NCT04031430). Women’s beliefs about medication (in general and during pregnancy) and adherence were assessed using the Beliefs about Medicine Questionnaire (BMQ) and the Probabilistic Medication Adherence Scale (ProMAS) administered during pregnancy (at inclusion), at 10–21 days and 4–6 months postpartum. Aspirin intake was self-reported in the MediSafe app. We did not intervene throughout the study.ResultsA total of 73 participants were recruited at a median gestational age of 14.1 weeks (IQR:13.2–15.6). The mean pregnancy BMQ scores for overuse and harm were 10.6 ± 2.9 and 8.8 ± 2.2 on a total score of 20, respectively. A total of 95% agreed to have a higher threshold for taking medicines during pregnancy and 50% disagreed with refraining from using medicines during pregnancy. Similar positive attitudes towards medicines were observed postpartum. The mean ProMAS score in pregnancy was 10.3 ± 3.9 out of 18. Similar rates were observed at 10–21 days postpartum, while a trend toward lower adherence was seen at 4–6 months postpartum (mean score 8.9 ± 4.5). The mean “minimal” and “maximal” self-reported aspirin intake was 82.5% and 98.6%, respectively. ProMAS scores were positively correlated with self-reported aspirin intake. Uncomplicated pregnancies showed higher ProMAS scores during pregnancy compared to complicated pregnancies.DiscussionWomen at risk for GHD involved in a clinical trial showed positive beliefs about medication use in general and during pregnancy throughout the perinatal period and reported high aspirin adherence rates. However, more research is needed to provide real-world adherence estimates in pregnancy and to assess the predictive utility of the ProMAS instrument to forecast adherence throughout pregnancy and adverse pregnancy and neonatal outcomes.Clinical Trial Registrationidentifier NCT04031430.